Effects of repeated potassium iodide administration on genes involved in synthesis and secretion of thyroid hormone in adult male rat. (15th October 2018) - Lebsir, Dalila; Manens, Line; Grison, Stephane; Lestaevel, Philippe; Ebrahimian, Teni; Suhard, David; Phan, Guillaume; Dublineau, Isabelle; Tack, Karine; Benderitter, Marc; Pech, Annick; Jourdain, Jean-Rene; et al.
Abstract: Background: A single dose of potassium iodide (KI) is recommended to reduce the risk of thyroid cancer during nuclear accidents. However in case of prolonged radioiodine exposure, more than one dose of KI may be necessary. This work aims to evaluate the potential toxic effect of repeated administration of KI. Methods: Adult Wistar rats received an optimal dose of KI 1 mg/kg over a period of 1, 4 or 8 days. Results: hormonal status (TSH, FT4) of treated rats was unaffected. Contrariwise, a sequential Wolff-Chaikoff effect was observed, resulting in a prompt decrease of NIS and MCT8 mRNA expression (−58% and −26% respectively), followed by a delayed decrease of TPO mRNA expression (−33%) in conjunction with a stimulation of PDS mRNA expression (+62%). Conclusion: we show for the first time that repeated administration of KI at 1 mg/kg/24h doesn't cause modification of thyroid hormones level, but leads to a reversible modification of the expression of genes involved in the synthesis and secretion of thyroid hormones. Highlights: KI prophylaxis over many days didn't induce any modification on thyroid hormonal status (TSH –FT3 and FT4 level). Repeated KI prophylaxis impacted reversibly the expression of genes involved in iodide transport, and thyroid hormone synthesis. The transcriptional effect was time-dependent.